Digital Vigilance: the Ethics of Network Communication and the Limits of Civilian Control - Anna V. Volkova (Евразийская интеграция: экономика, право, политика, 2019)
The article analyzes such a modern form of network civic activity as “digital vigilance”. It proves that digital vigilance as a challenge to digitalization is an interdisciplinary problem, it requires both conceptualization and serious empirical research. This study addresses issues of relations between the state and citizens in a networked, digital society, especially the formation of network ethics and analysis of the perception of citizens of the digital public space.